ҚАРАҚАЛПАҚСТАННЫҢ АРҚА РАЙОНЛАРЫ ЭТНОГИДРОНИМЛЕРИ - Мамбетова, Г.Ж. (ILIM hám JÁMIYET, 2018)
Some ethnohydronyms used in Karakalpak language are analyzed in the article. On the basis of the analysis of examples – ethnohydronyms of the northern regions of Karakalpakstan they are divided into three groups.